2021
DOI: 10.3389/fbuil.2021.635978
|View full text |Cite
|
Sign up to set email alerts
|

Educational Theory-Integrated Construction Industry Training: State-of-the-Art Review

Abstract: Workforce training is needed throughout the construction industry to create and maintain competent workers; unfortunately, most construction training and education research focuses on university student education. Integrating education science theory into construction training has the potential to improve industry training, but the status of this integration has not been well articulated. To address this gap, this article undertakes a state-of-the-art review of education theory–integrated construction training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Though the significant issues related to construction supervision practices were reported by several studies, only a few studies focused on the track of training development practices for improving the competencies of industry practitioners [12][13][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the significant issues related to construction supervision practices were reported by several studies, only a few studies focused on the track of training development practices for improving the competencies of industry practitioners [12][13][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education and training play a prominent role in the creation and maintenance of a capable workforce in the construction industry [27]. Jadallah et al [26] state that the training is effective when learning is promoted through theories developed within the field of education science that focus on how learners obtain, process and retain information. [25] reveal that questionnaire surveys are used by most firms to assess the competencies of trainees.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research by the authors found that there is a dearth of construction industry training programs in archival literature (Jadallah et al, 2021a); and opportunities exist to implement training programs coupled with optimal assessment methodologies grounded in established educational assessment research (Jadallah et al, 2021b). This study builds upon these findings by creating a process specific to construction materials for developing a construction training framework, as well as the developed framework.…”
Section: Introductionmentioning
confidence: 96%
“…The integration of practical learning experiences into construction management (CM) curriculum has garnered increased attention in recent years as educators aim to better prepare students for careers in the construction industry (Jadallah et al, 2021;Wetzel & Farrow, 2023). A growing body of research underscores the need to bridge the gap between theoretical knowledge and practical skills to equip graduates with the abilities to tackle real-world construction problems.…”
Section: Literature Reviewmentioning
confidence: 99%